Medicine saved ethics: Has ethics harmed medicine? - Carlo Petrini; Enrico Alleva (Istituto Superiore di Sanità, 2015)
In an article in The Boston Globe, Steven Pinker holds that the primary moral good of bioethics should be to "get out of the way". The accusation that bioethics is an obstacle to research because it calls attention to basic principles such as personal dignity and justice is clearly contradicted by the facts. There are, nonetheless, other ways in which bioethics can stand in the way of science, two of which, bureaucratisation and the loss of cultural vivacity, are worth addressing. Ethics committees provide a framework for evaluating problems and determining an appropriate course of action.